Coatings for Harsh Environments - Paul, Shiladitya (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The operation of numerous components that are critical to safety in industries around the world relies on protective coatings. These coatings often allow process equipment to serve a purpose in environments well beyond the operational limit of the uncoated components. Durability, ease of application, repairability, reliability and long-term performance of such coatings are all key to their application. Therefore, this book, Coatings for Harsh Environments, is devoted to research and review articles on the metallic, non-metallic and composite coatings used in aggressive environments. In particular, the topics of interest include, but are not limited to: coatings for high temperature and molten salt applications; thermal spray and cold spray coatings for aggressive environments; corrosion, wear and cavitation resistant coatings; coatings for mitigating marine corrosion; coatings for chemical and petrochemical plants; thermal barrier coatings.